2017
DOI: 10.5455/ajvs.246727
|View full text |Cite
|
Sign up to set email alerts
|

Organization of the Bronchial Associated Lymphoid Tissue (BALT) of The Dromedary Camel (Camelus Dromedarius)

Abstract: Key words: Camel, BALT, Bronchus, BronchiolesThe BALT is an organized lymphoid tissue in the mucosa of the bronchi and bronchioles that samples antigens leading to lymphocytes stimulation. This vital structure was studied in different species but not in the camel. Therefore this work studied the bronchi and bronchioles of 14 healthy camels of different ages (10 months -12 years) using light and transmission electron microscope. BALT was regularly present in all specimens studied. It was variable in locations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Several studies described the peculiar structures of the immune organs of the dromedary camel in different age without considering the BALT (Zidan et al 2000a , b ; Zidan and Pabst 2002 , 2012 ). In spite of that, the basic structure of the BALT of the one humped camel was describe before (Elhussieny et al 2017 ) and recently that of Bactrian camel (He et al 2019 ). There is no any available data about the age-related morphological changes of camel BALT.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies described the peculiar structures of the immune organs of the dromedary camel in different age without considering the BALT (Zidan et al 2000a , b ; Zidan and Pabst 2002 , 2012 ). In spite of that, the basic structure of the BALT of the one humped camel was describe before (Elhussieny et al 2017 ) and recently that of Bactrian camel (He et al 2019 ). There is no any available data about the age-related morphological changes of camel BALT.…”
Section: Introductionmentioning
confidence: 99%
“…The lung immune system can deal with all of these threats through a variety of specific mechanisms; one of them is the bronchus-associated lymphoid tissue (BALT) (Holt et al 2008 ) . BALT is a constitutive mucosal lymphoid tissue adjacent to major airway in some mammalian species, including camel (Elhussieny et al 2017 ), cattle (Anderson et al 1986 ), human and occasionally mice (Holt et al 2008 ), rats, and rabbits (Randall 2010 ) and absent in dogs and cats (Pabst and Gehrke 1990 ; Bienenstock and McDermott 2005 ). BALT is exposed to antigens from the airways and initiates local immune responses and maintains memory cells in the lungs (Randall 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that BALT distribution sites are inconsistent in different species. For example, BALT is located along the entire bronchial tree but mainly at the tracheal bifurcation in rabbits ( Bienenstock et al, 1974 ); between bronchi and arteries in mice and rats ( Breel et al, 1988 ; Gregson, Davey & Prentice, 1979 ); at small bronchi and bronchioles in Dromedary camels ( Elhussieny et al, 2017 ) and pigs ( Delventhal et al, 1992 ); and scattered in the total bronchial tree, but mainly in the lobar and segmental bronchi, in humans ( Richmond et al, 1993 ). Therefore, the BALT distribution characteristics in Bactrian camels were similar to those of Dromedary camels and pigs but more closely related to humans.…”
Section: Discussionmentioning
confidence: 99%
“…ILFs (the chief type) and ALFs were the two types of BALT in Bactrian camels. According to reports, these two types of BALT also exist in humans and the majority of animals (i.e., rabbits, mice, chickens, sheep, pigs and Dromedary camels) ( Bienenstock et al, 1974 ; Delventhal et al, 1992 ; Elhussieny et al, 2017 ; Foo & Phipps, 2010 ). However, unexpectedly, in the conducting portion of Bactrian camels, BALT was mainly located at the LP but was still found in the submucosa, under the muscular layer, and around the submucosal glands and cartilage.…”
Section: Discussionmentioning
confidence: 99%